Sarcopenia Impacts on Short- and Long-term Results of Hepatectomy for Hepatocellular Carcinoma - Voron, Thibault; Tselikas, Lambros; Pietrasz, Daniel; Pigneur, Frederic; Laurent, Alexis; Compagnon, Philippe; Salloum, Chady; Luciani, Alain; Azoulay, Daniel (Annals of surgery, 2015)
To evaluate the prevalence of sarcopenia among European patients with resectable hepatocellular carcinoma (HCC) and to assess its prognostic impact on overall and disease-free survival. Identification of preoperative prognostic factors in liver surgery for HCC is required to better select patients and improve survival. Recent studies have shown that preoperative discrimination of patients with low skeletal muscle mass (sarcopenic patients) using computed tomography was associated with morbidity and mortality after liver and colorectal surgery. Assessment of sarcopenia could be used to evaluate patients before hepatectomy for HCC. All consecutive patients who underwent hepatectomy for HCC in our institution, between February 2006 and September 2012, were included. Univariate and multivariate analyses evaluating prognostic factors of postoperative mortality and cancer recurrence were performed, including preoperative, surgical, and histopathological factors. Among 198 patients who underwent hepatectomy for HCC, 109 patients had an available computed tomographic scan and represent the study cohort. After a median follow-up of 21.23 months, 27 patients (24.8%) died. There were 20 deaths among the 59 patients who had sarcopenia and only 7 deaths in the nonsarcopenic group. Sarcopenic patients had significantly shorter median overall survival than nonsarcopenic patients (52.3 months vs 70.3 months; P = 0.015). On multivariate analysis, sarcopenia was found to be an independent predictor of poor overall survival (hazard ratio = 3.19; P = 0.013) and disease-free survival (hazard ratio = 2.60; P = 0.001). Sarcopenia was found to be a strong and independent prognostic factor for mortality after hepatectomy for HCC in European patients and could be used to evaluate eligibility of patients with HCC before surgery.